Pengungkapan Corporate Social Responsibility (CSR) Bank Umum Syariah Berdasarkan Islamic Social Reporting Index (Indeks ISR) - Apip Zanariyatim; Ai Nur Bayinah; oni sahroni (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2016)
The purpose of this study was to measure the extent to which the rate of ISR index scores when using the item more comprehensive. The population in this study was 12 BUS (Islamic Banks) and sample selection using purposive sampling BUS which has published the Annual Report 2012 to 2014 on the official website of each. The results obtained from this study is the ISR index score each year experienced a significant improvement in which the acquisition of ISR Index score is the highest in the year 2012-2014 BSM with a score of 89.6% and the lowest score achieved by BVS of 45.8%. The predicate obtained BUS until 2014 there were two BUS predicate Very Informative namely: BMI and BSM. Informative predicate achieved by BRIS, BSB, and BNIS. Then four BUS predicate Less Informative are: BMS, BCAS, BJBS, and BPS. While the two BUS more predicate Not Informative is BMS and BVS.